INTERCULTURAL COMMUNICATION SENSITIVITY IN GLOBAL ACADEMIC NETWORKING: EFL TEACHER TRAINEES’ PERCEPTIONS - Andi Rustandi; Iskhak Said; Jonathan Rante Carreon; Sazuliana Binti Sanif (Universitas Galuh, 2020)
The present study is aimed at uncovering EFL teacher trainees’ perceptions of intercultural communication sensitivity, required as their ways of facing global networking. Using intercultural sensitivity scale (ISS) proposed by Chen and Stratosta (2000), this survey involved the third grade of EFL teacher trainees (N=50) of a private teacher education college in Ciamis, West Java, Indonesia who had taken advanced language skill courses, pedagogical basics, teaching methodology, and cross-cultural understanding subject. The closed-ended questionnaires were administered to get their responses towards the options ranging from 1 to 5, the least and the most sensitive level. The percentage calculation of frequencies of the number of trainees’ responses revealed the trainees’ tendencies. The findings indicated that the trainees had positive perceptions of the necessity of having cultural sensitivity under three categories: engagement, enjoyment, and confidence. The finding suggests a high possibility for the Department to foster the trainees’ cultural competence for their own pedagogical considerations for their future teaching practices.Keywords: Intercultural Communication Sensitivity, Global Academic Networking, Cultural Competence.